Nourishing the Spirit: Exploratory Research on Ayahuasca Experiences along the Continuum of Recovery from Eating Disorders. Issue 5 (20th October 2017) - Lafrance, Adele; Loizaga-Velder, Anja; Fletcher, Jenna; Renelli, Marika; Files, Natasha; Tupper, Kenneth W.
ABSTRACT: Eating disorders (EDs) are serious health conditions that are among the most difficult to treat. Innovative treatments are needed and modalities from across cultures must be considered. Ayahuasca is a psychoactive plant-based tea originally used by Amazonian indigenous groups. A growing body of research points to its promise in the healing of various mental health issues. This study explored the potential therapeutic value of ayahuasca in the context of EDs, including the perceived impact of the preparatory diet and the ayahuasca purge. Sixteen individuals previously diagnosed with an ED participated in a semi-structured interview relating to their experiences with ceremonial ayahuasca drinking. Interviews were analyzed using thematic analysis. Themes presented relate to the reduction or cessation of ED and mental health symptoms, shifts in body perception, and the importance of a ceremonial setting and after-care. For some, the preparatory diet resulted in familiar patterns of concern; however, none felt triggered by the purge in ayahuasca. Ceremonial ayahuasca drinking shows promise in the healing of EDs and warrants further research.